2009
DOI: 10.1007/s11243-009-9273-1
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of the reduction of tetraoxoiodate(VII) by n-(2-hydroxylethyl)ethylenediaminetriacetatocobaltate(II) ion in aqueous perchloric acid

Abstract: The stoichiometries, kinetics and mechanism of the reduction of tetraoxoiodate(VII) ion, IO 4 -to the corresponding trioxoiodate(V) ion, IO 3 -by n-(2-hydroxylethyl)ethylenediaminetriacetatocobaltate(II) ion, [CoHED-TAOH 2 ] -have been studied in aqueous media at 28°C, I = 0.50 mol dm -3 (NaClO 4 ) and [H ? ] = 7.0 9 10 -3 mol dm -3 . The reaction is first order in [Oxidant] and [Reductant], and the rate is inversely dependent on H ? concentration in the range 5.00 9 10 -3 B H ? B 20.00 9 10 -3 mol dm -3 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The electronic spectrum of the complex gave λmax at 520 nm which was in agreement with literature value (Onu et al, 2009(Onu et al, , 2015.The result of spectrophotometric titration showed that two moles of the reductant were consumed by one mole of the oxidant. The plots of the titration from which the stoichiometry was determined is presented in Figure 1.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The electronic spectrum of the complex gave λmax at 520 nm which was in agreement with literature value (Onu et al, 2009(Onu et al, , 2015.The result of spectrophotometric titration showed that two moles of the reductant were consumed by one mole of the oxidant. The plots of the titration from which the stoichiometry was determined is presented in Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…The stoichiometry of the reaction was determined by spectrophotometric titration using the mole ratio method (Onu et al, 2009 and. The concentration of [Co(II)EDTA] 2was kept constant at 5.0 × 10 -3 mol dm −3 while that of S2O8 2was varied 4 folds below and above that of S2O8 2-.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the equilibrium in Equation 2has been established for hydrogen peroxide reactions, the nature of acid dependent obtained in this study coupled with the insensitivity of the reaction to change in ionic strength; envisaging an activated complex composed of anions ([CoHEDTAOH 2 ] − and 2 HO − ) is not supported by experimental result in this study. The mechanistic scheme below which involves a deprotonation of the complex specie [32]…”
Section: ) Catalysis Of Reaction By Added Anionmentioning
confidence: 99%
“…The stoichiometry of the reaction was control by spectrophotometric titration utilizing the mole ratio technique. The stoichiometry was assessed from a graph of absorbance against the mole ratio ( Onu et al., 2009 ).…”
Section: Methodsmentioning
confidence: 99%